2007
DOI: 10.1097/qad.0b013e3280b07b47
|View full text |Cite
|
Sign up to set email alerts
|

Week 24 efficacy and safety of TMC114/ritonavir in treatment-experienced HIV patients

Abstract: TMC114/r treatment resulted in greater virological and immunological responses in ART-experienced patients compared with CPI at 24 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 7 publications
2
59
0
Order By: Relevance
“…This potent activity against PI-resistant HIV indicates that this new antiretroviral molecule may be particularly useful for the treatment of patients who experience treatment failure with other PI-containing regimens. In the POWER randomized clinical studies, DRV-RTV (600/100 mg twice a day) plus an optimized background regimen was more effective than regimens containing control PIs at 24 weeks (9,14). Furthermore, these responses were sustained, lasting at least until week 48 (2), with satisfactory safety and tolerability in treatment-experienced patients.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This potent activity against PI-resistant HIV indicates that this new antiretroviral molecule may be particularly useful for the treatment of patients who experience treatment failure with other PI-containing regimens. In the POWER randomized clinical studies, DRV-RTV (600/100 mg twice a day) plus an optimized background regimen was more effective than regimens containing control PIs at 24 weeks (9,14). Furthermore, these responses were sustained, lasting at least until week 48 (2), with satisfactory safety and tolerability in treatment-experienced patients.…”
Section: Discussionmentioning
confidence: 86%
“…It has been suggested that HIV-1 is unlikely to develop significant resistance in patients treated with DRV, particularly if these patients have not previously been treated with other PIs (Y. Koh, T. Towata, A. K. Ghosh, and H. Mitsuya, presented In both studies, the twice-daily administration of 600/100 mg of DRV-RTV, respectively, was the most effective, with 53% of the patients in the POWER 1 study and 39% of those in the POWER 2 study showing decreases in viral loads to less than 50 copies per ml, whereas only 18% and 7% of the patients receiving control PIs in the two studies, respectively, showed such decreases in viral loads (9,14). This dose has recently been approved for use in the United States (Tibotec, October 2006) and several other countries for the treatment of HIV infection in antiretroviral treatment-experienced adult patients, including those with HIV-1 strains resistant to more than one PI.…”
mentioning
confidence: 99%
“…A new PI, darunavir (TMC114), has recently been shown to have considerable antiretroviral (ARV) activity in treatment-experienced patients. Darunavir boosted with low-dose ritonavir (RTV) (darunavir/RTV) led to significantly higher 24-and 48-week virological and immunological responses compared with currently available PIs in the POWER 1 and 2 (TMC114-C213 and TMC114-C202) studies in treatment-experienced HIVinfected patients, and was well tolerated [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…A new PI, darunavir (TMC114), has recently been shown to have considerable antiretroviral (ARV) activity in treatment-experienced patients. Darunavir boosted with low-dose ritonavir (RTV) (darunavir/RTV) led to significantly higher 24-and 48-week virological and immunological responses compared with currently available PIs in the POWER 1 and 2 (TMC114-C213 and TMC114-C202) studies in treatment-experienced HIVinfected patients, and was well tolerated [2][3][4].Given the need for lifelong antiretroviral therapy (ART), consideration of long-term toxicities is becoming increasingly important when choosing among different treatment regimens. It is therefore important to characterize the longterm tolerability profile of any new treatment, including DOI: 10.1111/j.1468-1293.00690.x HIV Medicine (2009 r 2009 British HIV Association 318 long-term metabolic abnormalities such as fat redistribution, dyslipidaemia, glucose intolerance and insulin resistance [5][6][7].…”
mentioning
confidence: 99%
“…12 Two randomized, controlled, phase IIb studies, POWER-1 (USA) and -2 (Europe), brought darunavir to the forefront of attention and led to an accelerated approval of darunavir for use in combination with ritonavir in adults with HIV strains that are resistant to other PIs. [13][14][15] In Romania the need for safety and efficacy data for darunavir used in subtype F HIV-1 ART-experienced patients was the starting point of this project. The primary aim of the current national multi-center prospective study was to evaluate the efficacy (CD4 cell count, viral load, and treatment compliance) of DRV/r and other ARV medications under marketed conditions in subtype F HIV-1 infected, treatment-experienced subjects in routine clinical practice in Romania.…”
Section: Introductionmentioning
confidence: 99%